Decoding the lncRNA-miRNA-mRNA network in sepsis-induced lung injury: from pathogenesis to extracellular vesicle-based therapy - Wei, Yating; Gong, Weiye; Wei, Yuhua; Jiang, Xiaohong; Li, Chaoqian; Ye, Rongzong (Frontiers in Immunology, 2026)
Sepsis-induced acute lung injury (S-ALI) represents a life-threatening condition with complex molecular pathophysiology and limited therapeutic options. Emerging evidence highlights the critical role of competing endogenous RNA (ceRNA) networks, particularly long non-coding RNA (lncRNA)–microRNA (miRNA)–mRNA axes, in orchestrating cell type-specific responses during S-ALI. This review synthesizes recent advances illustrating how these regulatory circuits modulate alveolar epithelial apoptosis, endothelial permeability, macrophage polarization, and neutrophil infiltration, thereby driving inflammation, barrier dysfunction, and immune dysregulation. Furthermore, we explore the promising therapeutic potential of engineered extracellular vesicles for targeted delivery of ceRNA components—such as miRNA mimics or lncRNA inhibitors—to precisely manipulate these networks. Despite progress, significant challenges remain, including model translatability, functional redundancy, and delivery efficiency. Overcoming these hurdles may unlock novel strategies for treating S-ALI, moving toward personalized and context-specific interventions.